Sex differences in psychiatric comorbidities of attention-deficit/hyperactivity disorder among children, adolescents, and adults: A nationwide population-based cohort study. - Pei-Hsin Kao; Chung-Han Ho; Charles Lung-Cheng Huang (PLoS ONE)
This cross-sectional, nationwide, population-based study aimed to elucidate sex differences in psychiatric comorbidities of Attention-deficit/hyperactivity disorder (ADHD) across children, adolescents, and adults. We analyzed data from Taiwan's comprehensive healthcare database, including 112,225 individuals diagnosed with ADHD, categorized by age (0-12, 13-18, ≥18 years) and sex. Psychiatric comorbidities were assessed using ICD-9-CM codes, focusing on age and sex-specific prevalence. Among the cohort, 83.50% were children (0-12 years) presenting primarily with learning disabilities and tics, while adolescents (13-18 years; 11.88%) had higher instances of oppositional defiant and conduct disorders. In adults (≥18 years; 4.62%), the prevalence of anxiety, depression, bipolar disorder, and substance misuse was notably higher. Males under 18 predominantly had ADHD, whereas females exhibited increased vulnerability to emotional disorders. In adulthood, males showed greater susceptibility to most psychiatric comorbidities, except sleep disorders. The study highlights the evolving nature of ADHD-related psychiatric comorbidities across different life stages, with distinct sex-based patterns. The transition from childhood to adulthood sees an increased prevalence of various psychiatric conditions, particularly impacting adult males. These findings underscore the need for age- and sex-specific therapeutic approaches in ADHD management. The cultural context of the study necessitates further research in diverse populations for broader applicability of the findings.